Resepsi Penonton terhadap Representasi Maskulinitas Hegemoni dalam Tokoh Utama Film Argylle - Dewanto, Muhammad Rizki Fauzan; Sanjaya, Andika (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to analyze audience reception of the representation of hegemonic masculinity in the main character of the film Argylle. The research employs a descriptive qualitative approach using the encoding/decoding reception analysis model. Data were collected through online interviews and literature review. Surveys were distributed randomly to informants to examine audience responses to gender stereotypes in Argylle. Thematic analysis was conducted in four stages: data reduction, data presentation, conclusion drawing, and critical interpretation. The findings reveal that audience perceptions of Elly Conway's character are divided into three reading positions. Some informants occupy the negotiated reading position, appreciating the portrayal of a strong and independent female character, yet questioning the consistency of the masculine traits depicted. Other informants are in the dominant reading position, accepting Elly’s representation positively as a symbol of women’s empowerment in a spy genre typically dominated by men. Meanwhile, one informant adopts an oppositional reading, considering Elly’s representation less realistic and overly divergent from traditional gender norms. These results indicate that gender is understood as a social construction negotiated based on audience experience and background. The film Argylle serves not only as entertainment, but also as a space for discussion and critical reflection on masculinity and gender representation in popular media.